Mentoringprozesse in der Lehrer:innenausbildung Gelingensbedingungen für Schulpraktika - Haas, Elisabeth (Verlag Julius Klinkhardt, 2021)
School mentoring in Austria is structurally anchored in the curricula of the new teacher trai-ning with the establishment/implementation of pedagogical-practical studies. Partner schools of universities of teacher education and universities offer students space for learning experience through practice and opportunity to complete the curricular parts of school in social environ-ment of schools. Mentors accompany and support the professionalization process and enter into a mutual learning and developmental relationship against the background of curricular re-quirement structures as well as subjective interpretative patterns. Transformational mentoring with a categorical breakdown to guide self-reflection is presented and discussed as a possible form of mentoring.In the research approach, interviews with mentors and students were conducted and evaluated with Grounded Theory. The central result of the study is that those involved in the dyadic rela-tionship want to build up or want to enter into a profession-specific learning and development process with the aim of furthering their own effectiveness and professionalism. Emanating from these studies, (training ) models for mentoring programs were constructed.